Decentralized voltage control with linear parameter-varying - (:unkn) unknown (Institute of Electrical and Electronics Engineers Inc., 2016)
The goal of this paper is to present a design of a voltage controller via state-feedback control. An efficient power system model to measure voltage and frequency is introduced. The model including uncertainties is admitted to be time-dependent, with a priori known upper and lower bounds. A method to solve the stabilization problem of the power system model subject to uncertain time-dependent parameters, which is quadratically stabilizable via linear state feedback is also introduced. The local information of each conventional generation unit is determined in a decentralized manner by the controller. The voltage controller utilizes its own local measurement only, and each local area utilizes in its own utility only. The voltage controller is also designed under the assumption that only the outputs are available for measurement. In order to find the quadratic stabilizability of the system via state feedback, one needs to solve a convex optimization problem which is characterized by Linear Matrix Inequalities (LMIs). Finally, the corresponding feedback gain of the voltage controller is constructed based on the feasible solution of the LMIs optimization problem. © 2016 IEEE.
Keywords: decentralized control; uncertain systems; uncertain time-varying parameters; Voltage Control